Analisis Pengaruh Segmentasi Gaya Hidup Terhadap Keputusan Penggunaan Dan Kepuasan Konsumen Jasa Simply Fresh Laundry Di Kota Pekanbaru - Hasanuddin, Roy; Musfar, Tengku Firli; ', Jushermi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This Research aim to to analyse comprehensive influence of eksogen construct which consist of Activity, Interest and Opinions on endogen construct which consist of Decision of Usage and Cutomer Satisfaction on Simply Fresh Laundry service in Pekanbaru City. In this research there are five variable that is Activity(X1), Interest(X2), Opinions( X3), Decision of Usage ( Y1) and Cutomer Satisfaction (Y2). Population of this research is all society who using Simply Fresh Laundry service in Pekanbaru City with sampel counted 150 selected responder use method of acidential sampling. In take of data at this research that is by giving kuesioner at responder. In analyse data, this research use method of Structural Equation Modelling ( SEM) constructively AMOS version 22. Result of this research indicate that Activity, Interest and Opinions in service of Simply Fresh Laundry in Pekanbaru City have an effect on Decision of Usage and Cutomer Satisfaction of Simply Fresh Laundry service in Pekanbaru City. In influence to Decision of Usage and Cutomer Satisfaction, Activity variable more dominant influence compared to Interest and OpinionsKeywords: Life Style, Activity, Interest, Opinions Decision Of Penggunaa, Decision of Usage, Cutomer Satisfaction, Simply Fresh Laundry